English as a foreign language teacher engagement with culturally responsive teaching in rural schools: Insights from China - Kong, Delin; Zou, Min; Chen, Jiaoyue (Frontiers in Psychology, 2022)
Culturally Responsive Teaching (CRT) has been found to promote student engagement and enhance learning in the classroom. As an effective pedagogy, the past decade has witnessed a soaring interest in exploring teachers’ competence, self-efficacy, and influencing factors in implementing CRT across school subjects. However, scant attention has been directed to language teachers’ engagement with CRT. Given the increasing diversity in students’ socio-economic status, cultural backgrounds, learning needs and preferences in English language classrooms, CRT has also become a prominent concern in China. This study sets out to explore EFL teacher engagement with CRT in rural schools in China. With a multi-case study of eight EFL teachers, the researchers collected data through individual interviews and classroom observations. Four types of teacher engagement based on the foci (i.e., knowledge and practice) were identified and were further characterised by cognitive, emotional, and social aspects. This study also taps into the internal and external factors influencing the teachers’ engagement with CRT. Implications and suggestions were provided to tackle the problems of English Language Education in rural China and contexts alike worldwide.